The Economic history of Britain since 1700 (Cambridge University Press, 1994)
An economic history of Britain since 1700, in three volumes by thirty-nine eminent historians and economists, this book will succeed the first edition of Floud and McClokey as a leading text book on its subject. The text has a firm economic basis, but emphasises the historical context and chronology and is written in straightforward and jargon-free English. It will appeal particularly to first and second year university student, but is also suitable for everyone interested in the history of the British economy. Volume 1 covers the period 1700 - 1860, that of Bristain's rise to relative economic supremacy.